The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/jmd-12-2015-0184
|View full text |Cite
|
Sign up to set email alerts
|

Analytical cognitive style moderation on promotion and turnover intention

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 80 publications
2
50
1
5
Order By: Relevance
“…Also, cognitive style does acts as moderator on relationship between servant leadership styles and leadership effectiveness. These results are in line with previous results of (Mughal & Busari, 2015;Khan, Mughal, & Khattak, 2017;Busari et al, 2017). Also found that cognitive style does acts as moderator on relationship between leadership and employees' performance and job satisfaction and turnover intention so does as moderator on servant leadership style and leadership effectiveness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, cognitive style does acts as moderator on relationship between servant leadership styles and leadership effectiveness. These results are in line with previous results of (Mughal & Busari, 2015;Khan, Mughal, & Khattak, 2017;Busari et al, 2017). Also found that cognitive style does acts as moderator on relationship between leadership and employees' performance and job satisfaction and turnover intention so does as moderator on servant leadership style and leadership effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studies were conducted in the past like (Bass & Avolio, 1995, Avolio & Bass, 2002Busari, 2011) on full range leadership model i.e. transformational, transactional leadership styles, laissez faire and leadership effectiveness with cognitive styles (Mughal & Busari, 2015;Busari, Mughal, Khan, Rasool & Kiyani, 2017). However, no such study has been conducted on cognitive style and leadership effectiveness by using the servant leadership style model given by Sendjaya (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Busari et al (2017)promosi jabatan adalah ketika seseorang bergerak dari satu posisi ke posisi yang lebih tinggi dengan tanggung jawab yang lebih besar. Pendapat serupa juga disampaikan oleh Siagian (2014:170), bahwa promosi jabatan didefinisikan sebagai perpindahan pegawai dari satu pekerjaan ke pekerjaan lain yang tanggung jawabnya lebih besar, tingkat hirarki jabatannya lebih tinggi dan penghasilannya pun lebih besar pula.…”
Section: Pendahuluanunclassified
“…In addition, management will outlay more costs in the attracting and training of new employees due to the high employees' turnover rate (Juhdi et al, 2013). Thus, employee turnover intention is very costly and has become a crucial factor that can affect the overall for organizational performance (Busari et al, 2017). Shah and Beh (2016) pointed out that employees' turnover intention is not only an issue in Western countries, but it is also a dangerous problem facing organizations in Asian countries.…”
Section: Introductionmentioning
confidence: 99%